PENGARUH KAPSUL EKSTRAK TEMULAWAK (Curcuma xanthorrhiza Roxb.) TERHADAP KADAR LDL DAN HDL KOLESTEROL PADA MENCIT HIPERLIPIDEMIA - Nurcahyani, Diah (Widya Warta, 2019)
Hyperlipidemia is an increase in blood lipid levels. Hyperlipidemia is strongly associated with changes in HDL levels and increases in LDL levels. One alternative natural ingredient toÂ  reduce cholesterol levels in the blood is ginger (Curcuma xanthorrhizaRoxb.). The purpose of this study was to determine the effect of capsules of temulawak extract (Curcuma xanthorrhizaRoxb.) on decreasing LDL and HDL cholesterol levels in hyperlipidemic mice. This study used 12 mice (Mus musculus L.). Models of hyperlipidemia animals were made with induction of egg yolk for 7 days. Therapy was carried out for 7 days with a curcuma xanthorrhizaRoxb extract capsule of 3x0.2 ml / day and 3x0.4 ml / day. The analysis used in this study is the One Way Analysis of Variance (ANOVA) with Duncan's advanced test for LDL and HDL levels. The results of the data analysis can be concluded that the curcuma xanthorrhizaRoxb Extract capsule significantly reduced LDL levels and significantly increased HDL levels in hyperlipidemic mice (Mus musculus L.).